Regiospecific Palladium-Catalyzed Cross-Coupling Reactions Using the Operational Equivalent of 1,3-Dilithiopropyne - Cabezas, Jorge A.; Ferllini, Natasha (Synthesis, 2020)
A regiospecific palladium-catalyzed cross-coupling reaction using the operational equivalent of the dianion 1,3-dilithiopropyne, with aromatic iodides is reported. This reaction gives high yields of 1-propyn-1-yl-benzenes and 2-(propyn-1-yl)thiophenes in the presence of catalytic amounts of palladium(0) or (II) and stoichiometric amounts of copper iodide. No terminal alkyne or allene isomers were detected. Reaction conditions were very mild and several functional groups were tolerated.
Keywords: 1,3-dilithiopropyne; cross coupling; 1-propynylbenzenes; 2-(propyn-1-yl)thiophenes; 2-phenyl-5-(propyn-1-yl)thiophene